Prediction of Reperfusion and Infarct Related Artery Patency after Thrombolysis in Acute Anterior Myocardial Infarction by Degree of P Wave Dispersion on ECG (Cardiovascular Journal, 2018)
Background: Early detection IRA patency following thrombolytic therapy is of great importance in terms of prognosis and identification of candidates for rescue percutaneous coronary intervention (PCI). P wave dispersion (PWD), a new parameter measured before and after thrombolytic therapy is supposed to predict successful reperfusion in patients with anterior acute myocardial infarction (AMI).Methods: 132 patients were selected and divided into two groups on the basis of ST Segment resolution (STR) after 120 minutes of thrombolysis. Group I: patients with STR >70%; Group II: patients with STR < 70%. P wave dispersion was measured in both groups before and after thrombolysis. All patients underwent coronary angiography (CAG). IRA was considered patent if TIMI flow grade was e”2.Results: It was observed that diabetes mellitus and dyslipidemia were significantly higher in group II patients (p=0.04 and p=0.03, respectively). PWD before thrombolysis (PWD0) and 90 minutes after thrombolysis (PWD90) in both groups were statistically insignificant (p=0.45 and p=0.19, respectively). The mean level of PWD120 was statistically significant (p=0.001). After multivariate regression analysis PWD120 was found to be the significant predictor of IRA patency (OR = 1.101; 95% CI = 1.012 – 1.240; p = 0.01).Conclusion: P wave dispersion in patients receiving thrombolytic therapy can be a predictor of successful reperfusion and patent IRA. PWD values, in combination with other reperfusion parameters, can contribute to the identification of rescue PCI candidates.Cardiovasc. j. 2018; 10(2): 158-163